Epidemiological Study of Hepatitis C Virus Infections and Their Genotypes in the Iraqi Population During 2022 - Tuama, Faiza L.; Dhedan, Azhar A.; Ghazzi, Jinan J.; Fadhil, Hula Y.; Najim, Alahin T. (Iraqi Journal of Science, 2026)
Background: The Hepatitis C virus (HCV) is thought to infect 170 million people globally, making it a viral pandemic. Most people with HCV infection progress to chronic illness, and infection with the virus is now the primary cause of liver transplantation. Objective: This paper assesses HCV infection prevalence and genotype distribution across fourteen provinces in Iraq, investigates the main reasons for virus transmission, and determines the correlation between viral load and infection with different genotypes/subtypes among the Iraqi population in 2022. Methods: In this epidemiological study, 738 specimens were analyzed using Enzyme-linked immunosorbent assay (ELISA), chemiluminescent immunoassay, real-time polymerase chain reaction (RT-PCR), and Western blot procedures to detect HCV infections. Results: Most specimens, 94.2%, tested positive for HCV, and various genotypes/subtypes were identified. The study found the highest frequency of HCV infections in June and a geographical prevalence with the most significant number of cases in Baghdad. Viral load analysis showed significant stratification across age groups, sex, and the presence of different viral genotypes/subtypes. It also showed that HCV infections were significantly associated with detection sources such as surgical procedures, renal failure, and thalassemia tests. Conclusion: This study underscores the importance of blood-borne transmission of HCV in Iraq and calls for enhanced preventive measures. The findings stress the need for effective therapies and potential vaccine development, given the global impact of HCV. The research is supported by references discussing hepatitis C spread and management, highlighting the challenges faced in different regions and patient demographics. Future research based on the findings presented in the referenced research paper should prioritize in-depth studies into the behavioral, medical, and socioeconomic factors contributing to the high prevalence of HCV in the Iraqi population. These could include longitudinal studies to monitor the long-term efficacy of preventive measures and treatment protocols in various demographic groups. Moreover, genetic studies would be beneficial in understanding the relationships between HCV genotypes/subtypes and disease progression or therapeutic outcomes better.